1987
DOI: 10.3168/jds.s0022-0302(87)79985-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Lactating Dairy Cows Fed Silage from Corn of Varying Maturities

Abstract: The deleterious effect of frost on corn harvested for silage was investigated with 30 lactating Holstein cows fed silages from corn harvested at the milk or dough stage, or after one, two, or five frosts. The fibrous components of the corn plant increased as maturity and dry matter content increased, whereas the mineral content tended to decrease. Dry matter intake and 4% fat-corrected milk increased as maturity of the silage increased up to the silage harvested after two frosts and then declined for the silag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A number of studies have shown that an increasing maturity of silage maize at harvest has a major effect on the DMI, milk yield and milk protein content of dairy cows . Summarizing data from 10 studies with 51 direct comparisons of maize silage, ensiled at different harvest maturity, on milk production and milk composition of dairy cows showed that the silage maize harvest maturity has a marked influence on the DMI, milk yield and milk protein content (Table ).…”
Section: Maize Silage and Dairy Cow Performancementioning
confidence: 99%
See 3 more Smart Citations
“…A number of studies have shown that an increasing maturity of silage maize at harvest has a major effect on the DMI, milk yield and milk protein content of dairy cows . Summarizing data from 10 studies with 51 direct comparisons of maize silage, ensiled at different harvest maturity, on milk production and milk composition of dairy cows showed that the silage maize harvest maturity has a marked influence on the DMI, milk yield and milk protein content (Table ).…”
Section: Maize Silage and Dairy Cow Performancementioning
confidence: 99%
“…Remarkably, most of the change in starch/NDF ratio occurred early in the grain‐filling period, because the growth of the kernels and the accumulation of nutrients in the kernels are very rapid during the early grain‐filling period, and the rate declines with progressing maturity. Moreover, the DMI generally decreases with increasing moisture content of the forages . Erdman suggested that the DMI of high‐moisture silages is more likely limited by the fermentation end products, a lower pH and high NH 3 levels.…”
Section: Maize Silage and Dairy Cow Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Average BW and BCS were unaffected by diet, but change in BW per period was negative for cows fed the GT diet. Previous research has shown small losses in BW when corn silage of greater than 40% DM was fed to lactating dairy cows (St-Pierre et al, 1987). 1 REF1 = Reference line 1 (Asgrow hybrid RX740), REF2 = reference line 2 (DEKALB hybrid DK647), CON = nontransgenic line (Asgrow hybrid RX670), CRW = corn rootworm protected line (event MON863).…”
Section: Methodsmentioning
confidence: 99%